Smoking-Related Behavior and Motivation to Quit Smoking Among Engineering Students at Universitas Pejuang Republik Indonesia - Juherah Juherah; Ridhayani Adiningsih; Erlani Erlani; Fajar Akbar; Erwinda Alwi Rachman (Jurnal Kesehatan Manarang, 2026)
Smoking prevalence among Indonesian university students remains alarmingly high, particularly among male students in engineering faculties; however, empirical evidence on the behavioral determinants of cessation motivation in this population is limited. Understanding the interplay between health knowledge, attitudes, and cessation-related actions is critical for designing evidence-based smoking cessation programs tailored to the university context. This study aimed to analyze the relationship between smoking-related behavior (knowledge, attitudes, and actions) and motivation to quit smoking among engineering students at Universitas Pejuang Republik Indonesia. An analytical observational study with a cross-sectional design was conducted. A total of 105 active smokers were recruited through purposive sampling from the Faculty of Engineering. Data were collected using a researcher-developed structured questionnaire comprising 40 Likert-scale items across four domains (knowledge, attitudes, actions, and motivation to quit). The instrument was validated through pilot testing (n=30) and demonstrated good internal consistency (Cronbach’s alpha: 0.78–0.85). Bivariate analysis was performed using chi-square tests and Fisher’s exact test with a significance level of α=0.05. The majority of respondents demonstrated good knowledge (96.19%), positive attitudes (92.38%), positive actions (77.14%), and high motivation to quit smoking (84.76%). Statistically significant associations were observed between motivation to quit smoking and knowledge (p=0.045; OR=4.89), attitudes (p=0.037; OR=5.23), and actions (p=0.044; OR=2.87). All three behavioral components were significantly associated with motivation to quit smoking. Attitudes demonstrated the strongest association, suggesting that university-based smoking cessation programs should prioritize attitude-modification strategies, such as motivational interviewing and peer support groups, complemented by behavioral skills training and smoke-free campus policies.